Ut pictura poesis: uma interpretação profética e poética da obra de Michelangelo - DOI: 10.5752/P.2175-5841.2012v10n25p75 - Amparo, Flávia Vieira da Silva do (Horizonte, 2012)
Poetry, in its broadest sense, emerges as a starting point for all knowledge about man and the world. The poet is not only an artist that writes verses, but one who seeks to intercede between the human and the divine. This article aims at studying the poetry and art of Michelangelo Buonarroti taking the concept of "Figure", as defined in the work of Auerbach, and analyzing the poetic work of the Italian artist and how it relates to prophetic themes. Both in the painting of the frescoes of the Sistine Chapel and in his poems, Michelangelo reveals the battle of the artist to assign a sense of transcendence, transforming Art in a divine revelation, which will require an interpretation of their readers. Grounded on this idea, the Italian genius blends Christian and pagan figures, such as Greco-Romans Sybils and Judeo-Christian prophets, to reread the past, interpret the present and foreshadow the future.